Lytic polysaccharide monooxygenase – A new driving force for lignocellulosic biomass degradation. (October 2022) - Guo, Xiao; An, Yajing; Liu, Fufeng; Lu, Fuping; Wang, Bo
Graphical abstract: Highlights: LPMOs significantly improve the conversion efficiency of lignocellulose. There are differences in the structure around the LPMOs active site. The relationship between the structure and function of LPMOs is explored. The preference of LPMOs for different electron donors is discussed. There is a preference for the host when LPMOs are heterologously expressed. Abstract: Lytic polysaccharide monooxygenases (LPMOs) can catalyze polysaccharides by oxidative cleavage of glycosidic bonds and have catalytic activity for cellulose, hemicellulose, chitin, starch and pectin, thus playing an important role in the biomass conversion of lignocellulose. The catalytic substrates of LPMOs are different and the specific catalytic mechanism has not been fully elucidated. Although there have been many studies related to LPMOs, few have actually been put into industrial biomass conversion, which poses a challenge for their expression, regulation and application. In this review, the origin, substrate specificity, structural features, and the relationship between structure and function of LPMOs are described. Additionally, the catalytic mechanism and electron donor of LPMOs and their heterologous expression and regulation are discussed. Finally, the synergistic degradation of biomass by LPMOs with other polysaccharide hydrolases is reviewed, and their current problems and future research directions are pointed out.